Archosauriform endocranial morphology and osteological evidence for semiaquatic sensory adaptations in phytosaurs. Issue 5 (4th August 2017) - Lessner, Emily J.; Stocker, Michelle R.
Abstract: The examination of endocranial data of archosauriforms has led to advances on the evolution of body size, nerve pathways, and sensory abilities. However, much of that research has focused on bird‐line archosaurs, resulting in a skewed view of Archosauria. Phytosauria, a hypothesized sister taxon to or early‐branching member of Archosauria, provides a potential outgroup condition. Most previous phytosaur endocranial studies were executed without the use of modern technology and focused on derived members of Phytosauria. We present a comparative CT examination of the internal cranial anatomy of Wannia scurriensis, the most basal known parasuchid phytosaur. Wannia scurriensis shows some overall similarity with extant crocodylians and derived phytosaurs in general endocranial shape, a large hypophyseal fossa, and trigeminal (CN V) innervation, but as a whole, the endocast has noticeable differences to crocodylians and other phytosaurs. The pineal region is expanded dorsally as in other phytosaurs but also laterally (previously unrecognized). CN V exits the pons in a more dorsal position than in Parasuchus hislopi, Machaeroprosopus mccauleyi, or Smilosuchus gregorii . Wannia scurriensis also exhibits a larger hypophyseal fossa relative to brain size than observed in P. hislopi or S. gregorii, which may indicate more rapid growth. The well‐preserved semicircular canals have lateral canals that are angled more anteroventrally than in derived phytosaurs. Extensive facial innervation from the large CN V indicates increased rostrum sensitivity and mechanoreceptive abilities as in Alligator mississippiensis . These endocranial similarities among phytosaurs and with Alligator indicate conserved ecological and functional results of an aquatic lifestyle, and highlight a need for further exploration of endocranial anatomy among Archosauriformes.